Colon stenosis due to acute neonatal appendicitis in a preterm baby: a case report - Takuto Naito; Hiromu Teramen; Hiroaki Hayashi; Mai Takegawa; Haruko Sakamoto; Toshihide Shimada; Koichi Ohno; Misao Yoshii (BMC, 2019)
Abstract Background Colon stenosis and acute appendicitis are rare diseases among premature babies. To the best of our knowledge, no study has identified both the conditions in preterm babies. Case presentation Here we report a case of a preterm Japanese male baby who developed ascending colon stenosis and appendicitis. During his neonatal intensive care unit stay, he developed increasing apnea and vomiting with rapidly worsening abdominal distention. Contrast radiographs indicated colon stenosis. Emergent exploratory laparotomy revealed ascending colon stenosis with appendix adhesion; both the lesions were surgically resected. The pathological findings suggested that he had appendicitis several weeks prior to the surgery; the onset of colon lesion seemed later than that of appendix. The perforated appendix was covered by the ascending colon, and inflammatory reactions led to the narrowing of the intestinal lumen. Conclusions Neonatal appendicitis and colon stenosis are both challenging for the diagnosis, and early laparotomy is necessary when these conditions are suspected.